Interferometric grazing incidence test of rough steep convex aspherics: full 3D reconstruction of the object - Rothau, Sergey; Schamburek, Tobias; Mantel, K.; Lindlein, Norbert (Applied Optics, 2022)
A grazing incidence interferometric measurement procedure is applied to test rough convex steep rotationally symmetric aspherics. The measurement of rough surfaces is possible; i.e., without the need to polish the surfaces, due to the large effective wavelength (λeff = 10 µm) of the test. One measurement step using diffractive beam splitters and phase-shifting techniques delivers the surface information along one meridian. The full surface description can be stitched together from several phase results combined with appropriate object rotations. This publication includes, besides the short recapitulation of the measurement principle and experimental setup, a presentation of the simulated and measured data of an aspherical object under test. The data analysis of each meridian is focused on the elimination of the misalignment aberrations caused by specimen displacements. Finally, the stitching of multiple meridian regions to a 3D surface map of the specimen is shown.
CRIS-Team Scopus Importer:2022-06-03